City as Part of the Spanish Cultural Code: The «Inside» and the «Outside» View - Yu. L. Obolenskaya (Ибероамериканские тетради, 2024)
The article seeks to determine the extent to which the national cultural code of the Spaniards is influenced by the designations of people’s place of residence or birth. The historical, cultural, etymological, psycholinguistic and conceptual analysis of such nominations as capital, ciudad, villa, pueblo, aldea, burgo reveals their role in the formation of the national and social identity of the Spaniards, as well as in their mythological, conceptual and linguistic picture of the world. The history and semantics of Spanish toponyms, the mythologems associated with them, as well as the structure of Spanish cities and the way of life there, which are reflected in the language people use, further justify the multicultural nature of their linguistic consciousness. Nearly 80 % of the country’s population perceive themselves as city residents, which is decisive for the social self-identification of Spaniards, as not only the residents of Madrid and other capitals of autonomous communities suffer from the ‘capital resident complex’, but also those who inhabit the ancient capitals of both Christian kingdoms and Muslim Spain of the «Al Andalus» era. The Spanish concepts of ciudad, villa, pueblo, capital and the history of the mythologem of Madrid are regarded as deep-rooted historical and cultural phenomena. Mentioning the symbolic cities of Sagunto, Numancia and Zaragoza, which also play a crucial role in the worldview of the Spanish, is equal to describing the heroism and resilience of the Spanish people. The «carnival element» and the love for puns, which clearly characterize both the national linguistic consciousness and the way the Spaniards speak, nurtured another mythologem — a small Andalusian town of Lepe acquired the status of «capital of jokes».